World Theoretical Perspectives on Heritage Studies and the Practical Research of Vietnam Woodblock’s Values - Nguyen Thi Thuy Linh, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Heritage is increasingly seen as inextricably linked to discourse and discursive practices. Assessing values is neither a simple nor a rapid task. The process is arduous and debatable because different stakeholders' values sometimes conflict. To gain critical knowledge of what cultural heritage is and does in current societies, how local contexts and varied cultural traditions affect and use heritage, it is tremendously beneficial to consider how such conservation and utilization are manifested on the global-local interface. Within those debates, the assessment of Vietnamese woodblock heritage and its values needs to be studied in-depth and systematically. There has still been a lack of complete understanding of the woodblocks in Vietnam. Although some types of woodblocks have been UNESCO recognized as a world documentary heritage site, few Vietnamese people know about their existence and values. This article aims to examine the contemporary perspectives dealing with heritage identification and values assessment in different countries and provides a first-step overview of their development and subsequent changes. Based on this, some comments are proposed to develop a further approach to woodblock’s values in Vietnam.Received 25th July 2022; Revised 10th September 2022; Accepted 29th September 2022